Project of developing the multimedia software supporting teaching and learning of English vocabulary - Lauc, Tomislava (Array, 2007)
Since the Academic Year 2005-2006 we have worked on a project of developing the interactive multimedia software for learning English vocabulary. The software was tested on junior learners in elementary school within the English language course lesson. The results were measured by comparing the test results from the computer- aided lesson with the ones from a traditional one and they showed a great level of disparity both regarding the learners’ knowledge and their motivation. Vocabulary of a language does not only consist of separate contextually independent words, but also of contextually bound lexical items, such as collocations. In 2006-2007 we have expanded the software by adding the feature for multimedia collocations. By terms of imitating reality, we have been designing multimedia animated presentations of English collocations comprising picture, text and sound. Our past, present and future phases of the project have purpose of examining the use of animation in educational settings.